DETERMINATION OF CONSUMER SATISFACTION IN ENDEK BALI FASHION MSMES - Made Ermawan Yoga Antara (Universitas Nusa Cendana, 2026)
This study examines the influence of digital promotion, brand image, and service quality on customer satisfaction at Fajar Sari Endek Collection in the context of the growing digital transformation in the local fashion industry. The rapid development of digital technology has significantly changed consumer behavior, requiring businesses to adopt effective digital promotion strategies, build a strong brand image, and deliver high service quality to maintain customer satisfaction. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to customers of Fajar Sari Endek Collection who had made purchases either directly or through digital platforms. The data were analyzed using multiple linear regression with the assistance of statistical software. The results indicate that digital promotion, brand image, and service quality each have a positive and significant effect on customer satisfaction, both partially and simultaneously. These findings suggest that integrating digital marketing strategies, strengthening a brand image rooted in local cultural values, and improving service quality are key factors in enhancing customer satisfaction in the traditional fashion industry. This study provides practical insights for managers of traditional fashion MSMEs in developing marketing strategies that are more customer-oriented and capable of sustaining competitiveness in the digital era. Keywords: Digital Promotion; Brand Image; Service Quality; Customer Satisfaction; Balinese Endek